Palliative care for people with non-malignant respiratory disease and their carers: a review of the current evidence. (September 2019) - Mc Veigh, Clare; Reid, Joanne; Larkin, Philip; Porter, Sam; Hudson, Peter
Background: Internationally, non-malignant respiratory disease is on the increase. However, although palliative care is recommended as an appropriate healthcare option for this client group, evidence suggests that these patients and their carers do not receive the same standards of palliative care as patients with a malignant lung condition. Aim: The aim of this review was to provide a critical overview of the current evidence base in relation to the palliative service provision for people with non-malignant respiratory disease and their carers. Methods: A review of the literature was conducted in July 2015 and updated in October 2017 and focused on the palliative care service provision for patients with interstitial lung disease, chronic obstructive pulmonary disease and bronchiectasis. Results: In total, 71 empirical studies were included in the review and grouped into two main themes: patient and carer's bio-psychosocial symptom needs and management, and palliative care service provision for patients with non-malignant respiratory disease and their carers. Conclusion: The majority of palliative research focuses on patients with a diagnosis of chronic obstructive pulmonary disease. A deeper insight is required into the palliative service provision experienced by those with other forms of non-malignant respiratory disease such as bronchiectasis and interstitial lung disease.